N‐glycosylated GPNMB ligand independently activates mutated EGFR signaling and promotes metastasis in NSCLC - Han, Chia‐Li (Cancer Sci, 2021)
Lung cancer is the leading cause of cancer‐related death worldwide. As well as the identified role of epidermal growth factor receptor (EGFR), its association with driver mutations has improved the therapeutics for patients with lung cancer harboring EGFR mutations. These patients usually display shorter overall survival and a higher tendency to develop distant metastasis compared with those carrying the wild‐type EGFR. Nevertheless, the way to control mutated EGFR signaling remains unclear. Here, we performed membrane proteomic analysis to determine potential components that may act with EGFR mutations to promote lung cancer malignancy. Expression of transmembrane glycoprotein non‐metastatic melanoma protein B (GPNMB) was positively correlated with the status of mutated EGFR in non‐small‐cell lung cancer (NSCLC). This protein was not only overexpressed but also highly glycosylated in EGFR‐mutated, especially EGFR‐L858R mutated, NSCLC cells. Further examination showed that GPNMB could activate mutated EGFR without ligand stimulation and could bind to the C‐terminus of EGFR, assist phosphorylation at Y845, turn on downstream STAT3 signaling, and promote cancer metastasis. Moreover, we also found that Asn134 (N134) glycosylation of GPNMB played a crucial role in this ligand‐independent regulation. Depleting N134‐glycosylation on GPNMB could dramatically inhibit binding of GPNMB to mutated EGFR, blocking its downstream signaling, and ultimately inhibiting cancer metastasis in NSCLC. Clarifying the role of N‐glycosylated GPNMB in regulating the ligand‐independent activation of mutated EGFR may soon give new insight into the development of novel therapeutics for NSCLC.